A comparative analysis of the profitability of pineapple-mango blend and pineapple fruit juice processing in Ghana - Asante , Michael K.; Kuwornu , John K. M. (Applied Studies in Agribusiness and Commerce, 2014)
This study analyzes the profitability of fruit juice processing using data from Kudors Fruit Juice Limited at Kasoa in Ghana. The cost involved in fruit juice processing (which includes the capital cost and the operating cost) was obtained from the Company. This study compares the profitability of blend (i.e. fruit juice made up of pineapple and mango blend) with that of pineapple juice alone. The viability of the project was determined using the discounted measures of project worth: Benefit-Cost Ratio (BCR), Net Present Value (NPV) and Internal Rate of Return (IRR). The empirical results reveal that pineapple juice processing had a BCR of 1.03 which means that going into the pineapple juice processing is profitable. The value of the NPV (GHS11,728.00) and IRR (23%) further confirms that pineapple juice processing is profitable because the NPV is positive and the IRR is greater than the discounted factor (21%). The results also showed that it is more profitable to invest in the blend (pineapple and mango blend) than the pineapple juice alone as it yields a BCR of 1.36 which was greater than the BCR of 1.03 for the pineapple juice only. Furthermore, the value of the NPV (GHS176,831.00) which is greater than the pineapple juice only, suggests that the blend is more profitable even though the IRR for both are the same. Moreover, it is also more likely to recover capital investment earlier in the processing of the blend than when one goes into pineapple juice processing only, because the net cash flow in year 2 (GHS 58,146.00) for the blend is more than triple that of the pineapple juice only (GHS17,826.00).These results have policy implications for the development of Agribusinesses in Ghana.